Rates of return to tertiary education: A study in human capital development in Malaysia for Year 2000. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2004)

(untitled)
Education is both a public good and a market commodity. As a public good, it is the responsibility of a responsible government to use scarce national resources for education in an optimal way. But as the government cannot meet all the demand for tertiary education, it has allowed private sector initiatives to set up private colleges to sell education as a commodity. Government and private individuals alike need to know the level of rates of return to their resources used in tertiary education to reflect the efficiency of the allocation of resources and the profitability of tertiary education as individual commitments.